Cost Margin Analysis of Cat Maintenance in Bantul Regency (International Journal of Scientific Research and Management (IJSRM), 2022)
The trend of having a pets, especially cats is happening all over the world, and Indonesia is no exception. In matters of animal care, owners are required to ensure the welfare of their cats. To be able to guarantee the welfare there are costs that must be incurred by the cats owner. This study aims to calculate and analyze the cost margin of cat maintenance care and its correlations with age, income, expenditure and knowledge of animal welfare of cat owners in Indonesia, especially in the Bantul area, Yogyakarta. The study was conducted using interviews via google form to 38 respondents who have cats as pets and then compared with data obtained from the field. The findings indicate that the factors of age, income and knowledge of animal welfare have a positive effect on the amount of expenditure used to finance the welfare of their cats. The outcome of this study can help owners and prospective cat owners to plan the costs needed to finance the welfare of cats according to their economic conditions. This study also suggest that cat owners should be more able to manage the expenditures according to their income while ensuring the welfare of their cats. Keywords: Income, Expenditure, Animal Welfare, Pets, Cats, Cost Margin